Applied Theater and Mixed-Status Families: A Collaborative Self-Study with Teacher Education Candidates. Issue 2 (4th May 2019) - Miller, Erin T.; Murray, Beth; Salas, Spencer
ABSTRACT: In this article, we narrate a self-study that emerged through a collaborative, arts-based inquiry around Latinx diversity, especially those arising from citizenship status at the individual and family level. Coming from distinct professional educational landscapes (theatre/drama education, middle/secondary education, and elementary education), we worked inter-disciplinarily to orchestrate a series of workshops for a cohort of elementary teacher education candidates. Our specific focus was rooted in the meanings that applied theatre teaching strategies suggested for us as teacher educators and for the teacher candidates we prepare to teach in schools. We also sought implications that might cultivate broader critical discourses within and across teacher education about diversity. Our blending of self-study with arts-based pedagogies was a purposeful effort to expand our students' and our own professional subjectivities by disrupting xenophobic and racialized public discourse about national borders using play-based strategies to foster risk and generativity.